Distribution network three-phase asymmetrical DC power flow calculating method - WEI ZHINONG; SUN GUOQIANG; CHEN SHENG; ZANG HAIXIANG; ZHOU JIAWEI (2016)
The invention discloses a distribution network three-phase asymmetrical DC power flow calculating method. Three-phase voltage and current phase angles are phase-shifted, and after phase shift, a three-phase model can meet the simplified assumption of traditional DC power flow. The method is applicable to the calculation of distribution network three-phase asymmetrical DC power flow. A simplified DC power flow model has the following characteristics: non-iterative calculation is adopted; both P-V coupling and Q-theta coupling are considered; the model is applicable to large R/X ratio of a distribution network; and the DC power flow solution includes voltage amplitude and voltage angle. Through the distribution network three-phase asymmetrical DC power flow calculating method proposed by the invention, quick calculation of distribution network three-phase asymmetrical power flow is realized, the Jacobian matrix of a power balance equation is constant, and the calculation efficiency of distribution network three